Nowoczesne mierniki wartości kreowanej przez przedsiębiorstwo - Kwiecień, Anna; Mucha, Beata (The Modern Measures of the Value Created by a Company, 2005)
In this article it was undertaken the trial of modem measures of the enterprise's value presentation - MVA, EVA, EBO and EVC. They complete measures used in analysis and estimation of economic condition of company, which are ranked among a group of traditional measures.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 286-298